Analyzing the Direction of the Stock Exchange Cycle - Yulyanah, Yulyanah; Manurung, Adler Haymans (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This research analyzes the direction of the stock market cycle and looks at the stock market prospects from January 2010 to September 2023. The methodology used in this research is the "decomposition method" and uses daily rate of return data during the research period. The research results show that the changes that occur in one day are greater than the changes that occur in the following days. The stock market is currently likely to experience a decline for the sixth cycle. There is no January effect in BEI but there is a December effect.